Approximation of the functions preset on the real axis by the Valle Pussen operators - Rukasov , V. I. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
Asymptotic equations for upper bounds of deviations of the de la Vallée-Poussin operators on C^βψ classes in the uniform metric are obtained.